2017
DOI: 10.1590/1519-6984.21215
|View full text |Cite
|
Sign up to set email alerts
|

Economic valuation of the ecosystem services provided by a protected area in the Brazilian Cerrado: application of the contingent valuation method

Abstract: Considering that the economic valuation of ecosystem services is a useful approach to support the conservation of natural areas, we aimed to estimate the monetary value of the benefits provided by a protected area in southeast Brazil, the Serra do Cipó National Park. We calculated the visitor's willingness to pay to conserve the ecosystems of the protected area using the contingent valuation method. Located in a region under intense anthropogenic pressure, the Serra do Cipó National Park is mostly composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
0
12
1
5
Order By: Relevance
“…The case of Brazilian rupestrian grasslands calls for profound scientific, conservation and political consideration due to their unparalleled biodiversity and levels of endemism, plus their strategic importance as a source of goods, including water, ornamental species, and scenic beauty for sustainable tourism, especially for the densely populated southeastern Brazil (Resende and Fernandes 2013;Resende et al 2017). Mountain environments in the Cerrado have until recently been relatively free from huge extensive cattle farming and habitat-aggressive plantations, such as soybean and sugar cane (Gibbs et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of Brazilian rupestrian grasslands calls for profound scientific, conservation and political consideration due to their unparalleled biodiversity and levels of endemism, plus their strategic importance as a source of goods, including water, ornamental species, and scenic beauty for sustainable tourism, especially for the densely populated southeastern Brazil (Resende and Fernandes 2013;Resende et al 2017). Mountain environments in the Cerrado have until recently been relatively free from huge extensive cattle farming and habitat-aggressive plantations, such as soybean and sugar cane (Gibbs et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A first step towards effective conservation of rupestrian grasslands is the translation, to all sectors of society, of the knowledge and importance of this ecosystem and the magnitude of the loss due to its conversion and misuse. For instance, the consequences of the loss of environmental services and of the overexploitation of natural resources leading to deterioration of human wellbeing is an aspect that needs to become appreciated (see Biénabe and Hearne 2006;Resende et al 2017). Conservation actions, however, are challenged by a number of basic limitations, including that the vast majority of the conservation units in the region lack planning, personnel, and the engagement of communities.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…This method has been applied in different assessments (e.g. Moreno-Sanchez et al, 2012;Nicosia et al, 2014;Siew et al, 2015;Resende et al, 2017). It has been demonstrated that putting an economic value to ecosystem services serves to support the conservation of certain areas (Resende et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this method, experts are consulted in certain contingencies of what they are willing to pay or willing to accept to pay. In Latin America, the contingent valuation method for protected natural areas is exhaustively used (Resende et al, 2017).…”
Section: Introductionmentioning
confidence: 99%